Prevalence of pineal gland calcification: systematic review and meta-analysis - Daniel Gashaneh Belay; Misganaw Gebrie Worku (Systematic Reviews, 2023)
Abstract Background Pineal gland calcification is the formation of corpora arenacea predominantly composed of calcium and phosphorus. It plays an important role in regulating the light/dark circadian changes to synchronize their daily physiological activities like feeding, metabolism, reproduction, and sleep through the secretion of melatonin. Therefore, this study aimed to assess the pooled prevalence of pineal gland calcification. Methods A systematic review was done using published research articles from different electronic databases. Cross-sectional studies were included for systematic review and only studies conducted on the human population were included for quantitative analysis. Published articles were selected by assessing the title and abstract for relevance to the review objectives. Finally, the full text was retrieved for further assessment. Results The pooled prevalence of pineal gland calcification was 61.65% [95% CI: 52.81, 70.49], with a heterogeneity of I 2 = 97.7%, P ≤ 0.001. According to the qualitative analysis, an increase in age, male sex, and white ethnicity are the major socio-demographic characteristics that increase the prevalence of pineal gland calcification. Conclusion The pooled prevalence of pineal gland calcification was higher compared with reports from previous studies. Different studies reported pineal gland calcification was most prevalent in the adult population compared with the pediatric age groups. According to the qualitative analysis, an increase in age, male sex, and white ethnicity are the major socio-demographic characteristics that increase the prevalence of pineal gland calcification.